Association of pentraxin in periodontitis patients with coronary artery disease - Paavai Ilango; Jaideep Mahendra; Little Mahendra; Sanjay M Cherian; Vasugi Suresh; Arulpari Mahalingam; V Vinoth Khanna; Abirami Thanigaimalai (Wolters Kluwer Medknow Publications, 2023)
Objectives: Pentraxin 3 (PTX3) is a biomarker, associated with the pathogenesis of Periodontitis and coronary artery disease (CAD) individually, but their role in patients with both diseases remains unclear. The current study aims to evaluate the association of PTX in patients with concomitant periodontitis and CAD. Materials and Methods: In a case-control study, 240 participants were selected and divided into four groups. Nonperiodontitis + noncardiac = 60 patients, periodontitis + noncardiac (P + NC) = 60 patients, nonperiodontitis + cardiac (NP + C) = 60 patients, periodontitis + cardiac (P + C) = 60 patients. Demographic variables, cardiac and periodontal parameters were recorded. PTX was evaluated in the subgingival plaque and atheromatous plaque samples using real-time quantitative polymerase chain reaction and compared between the groups. The results were statistically analyzed. Results: Among the demographic variables, age showed a significant difference between the groups. Systolic and diastolic blood pressure, low-density lipoprotein, and random blood sugar were significantly higher in NP + C and P + C groups (P ≤ 0.05). The plaque index, probing pocket depth, and clinical attachment loss were significantly higher in P + NC and P + C groups (P ≤ 0.05). PTX was significantly elevated in P + C group (P = 0.000). Pearson's correlation revealed a significant correlation between the periodontal parameters and PTX in both the cardiac and oral samples. Conclusion: PTX3 levels were elevated in CAD patients with periodontitis suggesting the influence of periodontal inflammation in the progression of CAD. PTX3 may serve as a diagnostic and prognostic tool for both periodontitis and CAD. This study could provide an understanding and awareness about the potential role of PTX3 in both periodontitis and CAD.